2019
DOI: 10.1111/cup.13613
|View full text |Cite
|
Sign up to set email alerts
|

An abdominal wall mass of exogenous insulin amyloidosis in setting of metastatic sarcoma

Abstract: Exogenous insulin amyloidosis (AIns) is an iatrogenic form of amyloidosis which is found in diabetic patients, generally localized to the site of subcutaneous insulin administration. It may form a discrete mass that could come to clinical attention, and can contribute to abnormal pharmacokinetics of the exogenous insulin, resulting in worsened control of diabetes. In this case report, we describe such a lesion in a 72‐year‐old man with a history of type 2 diabetes and primary adrenal gland epithelioid sarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Eighteen (81.8%) of 22 studies performed HE staining and reported “foreign body giant cells,” “eosinophilic,” “inflammation,” “amorphous,” and “keratosis” as observations 17–33 . Twenty (90.9%) of 22 studies performed Congo red staining and reported green birefringence when viewed with polarized light, consistent with amyloid deposits 3,9,17–21,24–36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen (81.8%) of 22 studies performed HE staining and reported “foreign body giant cells,” “eosinophilic,” “inflammation,” “amorphous,” and “keratosis” as observations 17–33 . Twenty (90.9%) of 22 studies performed Congo red staining and reported green birefringence when viewed with polarized light, consistent with amyloid deposits 3,9,17–21,24–36 .…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen (81.8%) of 22 studies performed HE staining and reported "foreign body giant cells," "eosinophilic," "inflammation," "amorphous," and "keratosis" as observations. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Twenty (90.9%) of 22 studies performed Congo red staining and reported green birefringence when viewed with polarized light, consistent with amyloid deposits. 3,9,[17][18][19][20][21][24][25][26][27][28][29][30][31][32][33][34][35][36] Fifteen (68.1%) of 22 studies performed immunohistochemical (IHC) staining for insulin and reported that LIDA was positive for insulin.…”
Section: Outcome Parameters With Lida In This Scoping Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Since AIns was first reported in 1983, 1 over 25 cases have been noted in the literature. 2 The classic clinical presentation is a firm, asymptomatic plaque or subcutaneous nodule 3 at a frequent injection site. Histopathologic examination classically demonstrates homogeneous eosinophilic material and apple-green birefringence with Congo red staining.…”
Section: Discussionmentioning
confidence: 99%